Factors associated with resident‐to‐resident elder mistreatment in nursing homes. Issue 4 (27th December 2021) - Pillemer, Karl; Silver, Stephanie; Ramirez, Mildred; Kong, Jian; Eimicke, Joseph P.; Boratgis, Gabriel D.; Meador, Rhoda; Schultz, Leslie; Lachs, Mark S.; Nolte, Julia; Chen, Emily K.; Teresi, Jeanne A.
Abstract: Background: Resident‐to‐resident elder mistreatment (RREM) in nursing homes has serious physical and psychological consequences, but factors related to RREM occurrence remain unclear. This study identifies individual and environmental characteristics associated with involvement in RREM episodes. Methods: The design was an observational study carried out in five urban and five suburban New York state nursing homes randomly selected on the basis of size and location. The sample consisted of 2011 residents in 10 facilities; 83% of facilities and 84% of eligible residents participated. RREM and potential correlates were identified through resident interviews, staff interviews, shift coupons, observation, chart review, and accident or incident reports. Results: A multivariate analysis controlling for relevant covariates found that individuals involved in RREM incidents exhibit milder dementia, show behavioral symptoms, and are less functionally impaired. Although special care units (SCU) for dementia have benefits for residents, one potential hazard for SCU residents is elevated risk for RREM. Conclusions: Interventions to prevent and intervene in RREM incidents are greatly needed. The correlates identified in this research point to the need for targeted interventions, specifically for residents with milder impairment and with behavioral symptoms and individuals in SCUs.